THE EFFECTIVENESS OF FOOD SECURITY DIMENSIONS ON FOOD SECURITY IN LANDLOCKED DEVELOPING COUNTRIES - Nur Marina Abdul Manap (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Food security is an important issue that has been discussed all over the world. Achievement in food security is based on the Food and Agriculture Organization (FAO policy) and depends on four important indicators known as availability, accessibility, utilization, and stability. This paper examines the effectiveness of the food security dimension on food security in Landlocked Developing Countries. The static panel data was adopted using a fixed-effect model to measure the effectiveness of food security dimensions on DES. The findings of this study showed that food security dimensions played a very important role in affecting the DES in landlocked developing countries. An increase in food availability, food accessibility, food utilization, and food stability were found to positively impact food security achievement in Landlocked developing countries.